2018
DOI: 10.1007/s10346-018-1043-8
|View full text |Cite
|
Sign up to set email alerts
|

Residual-state creep of clastic soil in a reactivated slow-moving landslide in the Three Gorges Reservoir Region, China

Abstract: We study the creep properties of clastic soil in residual state. The intact samples are taken from a reactivated slow-moving landslide in the Three Gorges Reservoir Region, China. Firstly, the patterns of the landslide movement are analysed based on recent monitoring data, which indicate that the soil within the shear zone is undergoing two deformation processes: a creep phase, characterised by different creep rates, and a dormant phase. We then study the creep behaviour of the soil samples through a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 43 publications
(57 reference statements)
0
32
0
Order By: Relevance
“…Thus, we utilize the reciprocal value of F sb to be the landslide intensity in this study. The relationship between building vulnerability and the landslide intensity was fitted by employing a Weibull (1951) function that produces an S-shaped curve. This type of distribution curve has been proved to be the best for physical vulnerability analysis by Papathoma-Köhle et al (2015).…”
Section: General Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we utilize the reciprocal value of F sb to be the landslide intensity in this study. The relationship between building vulnerability and the landslide intensity was fitted by employing a Weibull (1951) function that produces an S-shaped curve. This type of distribution curve has been proved to be the best for physical vulnerability analysis by Papathoma-Köhle et al (2015).…”
Section: General Functionsmentioning
confidence: 99%
“…Slow-moving landslides are observed worldwide in many countries, e.g. Italy (Cascini et al, 2008;Antronico et al, 2015;Uzielli et al, 2015a;Borrelli et al, 2018;Ferlisi et al, 2019), Canada (Clifton et al, 1986;Brooker and Peck, 1993;Moore et al, 2006;Barlow, 2000), China (Chen et al, 2016;Zhang et al, 2018;Dong et al, 2018;Wang et al, 2018), the USA (Esser, 2000), and Australia (Jworchan et al, 2008). Fell et al (2008) suggested the estimation of the physical vulnerability of elements at risk for various landslide types.…”
Section: Introductionmentioning
confidence: 99%
“…All evidence indicates that the No. 1-1 riverside sliding mass exhibits the largest deformation, revealing the most fragile part of the landslide [47,50].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of the reactivated landslides exhibited severe deformation during the drainage period; however, approximately 16% of the landslides deformed during the filling stage [15]. A large number of previous studies have shown that the deformation characteristics of these landslides are affected by the hydraulic conditions (e.g., the fluctuation rate of the water level) and the material properties (e.g., permeability and mechanical strength) [19][20][21]. However, further efforts are needed to evaluate the behavior of the macro-geological model.…”
Section: Introductionmentioning
confidence: 99%